Pengaruh Edukasi Gizi dengan Media Video Motion Graphics Terhadap Pengetahuan dan Sikap Tentang Obesitas Remaja - Ramadhanti, Fernandita Mutiara; Sulistyowati, Enik; Jaelani, Mohammad (Universitas Muhammadiyah Semarang, 2022)
The prevalence of adolescents with obesity is 4.8%. Nutrition knowledge andadolescent attitudes are the factors that can affect obesity. Video plays a vital media forconveying nutrition-related information. This was experimental with pre-posttest control group design. Subjects were 48 juniorhigh school students divided into 2 groups randomly. The treatment group receiving nutritioneducation by video (n=24) and the control group using poster (n=24). A statistical analysis ofWilcoxon and paired t-test were used to analyze difference before and after treatmentrespectively, while the group different was analyzed using Mann Whitney and independent ttest.Theaverageknowledgescoreintreatmentgroupincreasedby17.29points(p=0,000)andin control group by 7.71 point (p=0.000) from baseline. The average attitude score intreatment group increased by 10.16 points (p=0.000) and in control group by 3.96 point(p=0.003) from baseline. A significant different in the score of knowledge between thetreatment and control group (p=0.015) was observed. The score of attitude between thetreatment and control group was also significantly different (p=0.012). Nutrition education using video media may an effective approach to increaseknowledge and attitudes of obesity aspect in the adolescence. Keywords: Obesity; Knowledge; Attitude; Video; adolescents